2013
DOI: 10.1007/s00221-013-3581-6
|View full text |Cite
|
Sign up to set email alerts
|

Noise-enhanced kinaesthesia: a psychophysical and microneurographic study

Abstract: We first explored whether the ability of subjects to detect the direction of slow ramp imposed movements may be improved by the application of mechanical noise to muscle tendons. Movements were plantar/dorsal flexion of the ankle at 0.04°/s, and the amplitude was just sub-threshold for each subject. A white noise signal (random vibration), low-pass filtered to 100 Hz and distributed uniformly in amplitude, was applied to both the extensor and the flexor ankle muscle tendons with four different mean amplitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 34 publications
1
36
1
1
Order By: Relevance
“…More specifically, anesthetic procedures have indicated that such potentials are associated with the activation of muscle spindles, with little (if any) contribution from cutaneous and joint receptors (Abbruzzese et al, 1985;Starr et al, 1991;Mima et al, 1996). In addition, microneurographic techniques have shown that the essential proprioceptive sources of kinesthetic information of limb movement are the muscle spindles (Burgess et al, 1982;Burke et al, 1988), whereas cutaneous afferents have been shown to be partially active (Aimonetti et al, 2007) or even inactive (Ribot-Ciscar et al, 2013) during passive movement. In this sense, the N1 component observed in the present study must have been triggered by the discharges of muscle spindles from the triceps surae muscles.…”
Section: N1 Componentmentioning
confidence: 98%
See 1 more Smart Citation
“…More specifically, anesthetic procedures have indicated that such potentials are associated with the activation of muscle spindles, with little (if any) contribution from cutaneous and joint receptors (Abbruzzese et al, 1985;Starr et al, 1991;Mima et al, 1996). In addition, microneurographic techniques have shown that the essential proprioceptive sources of kinesthetic information of limb movement are the muscle spindles (Burgess et al, 1982;Burke et al, 1988), whereas cutaneous afferents have been shown to be partially active (Aimonetti et al, 2007) or even inactive (Ribot-Ciscar et al, 2013) during passive movement. In this sense, the N1 component observed in the present study must have been triggered by the discharges of muscle spindles from the triceps surae muscles.…”
Section: N1 Componentmentioning
confidence: 98%
“…As measurements of performance, both are limited in quantifying possible proprioceptive impairment per se (e.g., proprioceptive loss due to aging or neuropathy) since both measurements can be also influenced by cognitive and motor factors. A promising approach for investigating the neurophysiological aspects of proprioceptive function is the association of passive joint movement to different techniques such as microneurography (Burke et al, 1988;Ribot-Ciscar et al, 2013), electroencephalography (EEG) (Cassim et al, 2001;Lewis and Byblow, 2002;Seiss et al, 2002;Keinrath et al, 2006), and transcranial magnetic stimulation (TMS) (Lewis et al, 2001;Lewis and Byblow, 2002). The combination of these techniques can be very useful in the study of how different stages of information transmission and processing are involved in a cognitive sensorimotor task.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the application of an optimal-amplitude random mechanical vibration to both the extensor and flexor ankle muscle tendons was shown to improve the detection of imposed ankle movements that were initially subthreshold. In addition, microneurographic recordings revealed improved muscle spindle responses during the application of an optimal level of mechanical vibration to muscle tendons (Cordo et al 1996;Ribot-Ciscar et al 2013). In the present study, mechanical noise was applied to both the gastrocnemius/soleus (GS) muscles and the tibialis anterior (TA) muscle to optimize ankle proprioceptive cues.…”
Section: Introductionmentioning
confidence: 97%
“…We used this method because the effects of mechanical stimulation on neuromuscular function have been accurately described and provide a solid basis for understanding the potential postural effects. Indeed, improved movement detection due to the induction of stochastic resonance by mechanical stimulation was recently demonstrated for the first time (Ribot-Ciscar et al 2013). More specifically, the application of an optimal-amplitude random mechanical vibration to both the extensor and flexor ankle muscle tendons was shown to improve the detection of imposed ankle movements that were initially subthreshold.…”
Section: Introductionmentioning
confidence: 98%
“…Patients may also have a reduced ability to use afferent feedback to drive the gradual adaptation we observed in uninjured participants. If this is found to be true, then enhancing proprioceptive feedback with techniques such as white noise tendon vibration (Ribot-Ciscar et al 2013) may hold promise for improving function, similar to the beneficial effects of foot sole vibration on balance (Priplata et al 2006). …”
Section: Discussionmentioning
confidence: 99%